The effectiveness and resilience of phosphorus management practices in the Lake Simcoe watershed, Ontario, Canada. Issue 9 (17th September 2016) - Crossman, J.; Futter, M. N.; Palmer, M.; Whitehead, P. G.; Baulch, H. M.; Woods, D.; Jin, L.; Oni, S. K.; Dillon, P. J.
Abstract: Uncertainty surrounding future climate makes it difficult to have confidence that current nutrient management strategies will remain effective. This study used monitoring and modeling to assess current effectiveness (% phosphorus reduction) and resilience (defined as continued effectiveness under a changing climate) of best management practices (BMPs) within five catchments of the Lake Simcoe watershed, Ontario. The Integrated Catchment Phosphorus model (INCA‐P) was used, and monitoring data were used to calibrate and validate a series of management scenarios. To assess current BMP effectiveness, models were run over a baseline period 1985–2014 with and without management scenarios. Climate simulations were run (2070–2099), and BMP resilience was calculated as the percent change in effectiveness between the baseline and future period. Results demonstrated that livestock removal from water courses was the most effective BMP, while manure storage adjustments were the least. Effectiveness varied between catchments, influenced by the dominant hydrological and nutrient transport pathways. Resilience of individual BMPs was associated with catchment sensitivity to climate change. BMPs were most resilient in catchments with high soil water storage capacity and small projected changes in frozen‐water availability and in soil moisture deficits. Conversely, BMPs were less resilient in catchments with larger changes in spring melt magnitude and in overland flow proportions. Results indicated that BMPs implemented are not always those most suited to catchment flow pathways, and a more site‐specific approach would enhance prospects for maintaining P reduction targets. Furthermore, BMP resilience to climate change can be predicted from catchment physical properties and present‐day hydrochemical sensitivity to climate forcing. Key Points: Management strategy effectiveness varied by dominant hydrological and nutrient transport pathways Strategy resilience can be predicted from catchment physical properties and climatic sensitivity Using strategies which target dominant nutrient pathways optimizes sustainable nutrient reductions